2022
DOI: 10.1186/s12911-022-01860-3
|View full text |Cite
|
Sign up to set email alerts
|

The development and implementation of a guideline-based clinical decision support system to improve empirical antibiotic prescribing

Abstract: Background To describe and evaluate a clinical decision support system (CDSS) for empirical antibiotic therapy using a systematic framework. Methods A reporting framework for behavior change intervention implementation was used, which includes several domains: development, evaluation and implementation. Within the development domain a description is given of the engagement of stakeholders, a rationale for how the CDSS may influence antibiotic presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Digitalization can also enhance AMS processes and help overcome challenges associated with implementing these processes (23). For example, clinical decision support systems (CDSS) can aid physicians in correctly diagnosing bacterial infections and guiding the choice of empiric antibiotic therapy (37)(38)(39)(40). By combining a patient's bio-data, clinical history and diagnostic results (i.e., laboratory and radiological) CDSS can facilitate improved clinical decision-making, optimized antimicrobial therapy and better treatment outcomes (37)(38)(39)(40).…”
Section: Emerging Opportunitiesmentioning
confidence: 99%
“…Digitalization can also enhance AMS processes and help overcome challenges associated with implementing these processes (23). For example, clinical decision support systems (CDSS) can aid physicians in correctly diagnosing bacterial infections and guiding the choice of empiric antibiotic therapy (37)(38)(39)(40). By combining a patient's bio-data, clinical history and diagnostic results (i.e., laboratory and radiological) CDSS can facilitate improved clinical decision-making, optimized antimicrobial therapy and better treatment outcomes (37)(38)(39)(40).…”
Section: Emerging Opportunitiesmentioning
confidence: 99%
“…Carefully designed decision tools not only provide prescribers with more detailed information, but also have the additional potential to reduce intuitive or heuristic decision making and thereby decrease the harmful influence of cognitive biases. Indeed, previous trials of computerised decision support systems have shown such tools' potential to improve clinical decision making, although adherence to the system's recommendations and correct system use are likely to be prerequisites [34].…”
Section: Decision Supportmentioning
confidence: 99%